Increasing Wave Energy Moves Arctic Continental Shelves Toward a New Future. Issue 9 (7th September 2022) - Malito, John; Eidam, Emily; Nienhuis, Jaap
Abstract: Arctic continental shelves, including the Alaskan Beaufort Shelf (ABS), are experiencing declines in sea ice coverage leading to increasingly energetic sea states and coastal erosion. In this study we investigated the morphologic response of the ABS to increasing wave energy, and how shelf profile adjustments modify wave energy propagating toward the coast. We developed a 2D cross‐shelf morphodynamic model using Delft3D and tested shelf response to a present‐day wave climate and a future Arctic wave climate projected under the RCP8.5 climate‐change scenario. Simulations lasting 1000 years were conducted for relatively steep (Flaxman Island, AK, slope 0.0008) and flat (Harrison Bay, AK, slope 0.0003) cross‐shelf profiles. We found that morphologic evolution and regulation of future waves depends primarily on existing shelf morphology. On the steeper profile, RCP 8.5 waves drove sediment erosion at 0–15 m water depth and redeposition at 15–30 m water depth. Over 1000 years, this redistribution of sediment from the inner to middle shelf resulted in a 7.6% reduction in wave heights at the 2 m isobath. This morphologic adjustment represented a regulatory feedback in which shallowing of the middle shelf led to attenuation of waves reaching the inner shelf. In contrast, effective wave attenuation across the flatter and wider Harrison Bay section limited cross‐shelf transport and morphologic change under both wave climates. Together our results suggest that coastal changes in response to the growing Arctic wave climate may be dependent on shelf morphology, and even mitigated in some regions by morphologic adjustment. Plain Language Summary: In recent decades, declining Arctic sea ice has led to increasingly energetic waves that persist for longer periods throughout the year, thereby accelerating coastal erosion and posing a threat to coastal communities and ecosystems. However, waves are modified as they travel across the continental shelf, making the shelf a key factor in how shorelines are impacted by wave energy. A sediment transport model was developed to test how present‐day and projected future waves can impact shelf evolution, and how shelf geometry can influence the character of waves reaching the coast. Our results showed that a relatively steep Arctic shelf section was more sensitive to the growing wave climate. Enhanced waves drove greater erosion on the inner shelf and deposition of these sediments on middle shelf. The redistribution of sediments from the inner shelf to the middle shelf led to attenuation of projected waves as the shelf evolved over time, reducing the relative impact of greater future waves. In contrast, a relatively flat shelf section damped wave energy, and reduced the potential for changes in the continent shelf shape. These results suggest that the shape of a continental shelf can impact how increasingly large waves are felt at the coastline. Key Points: A morphodynamic model was developed to explore feedbacks between Arctic continental shelves and growing sea states related to sea‐ice losses On a higher‐relief shelf section, stronger waves drove offshore sediment transport and mid‐shelf deposition which regulated wave energy A lower‐relief shelf section was relatively insensitive to morphologic adjustment under larger waves due to effective wave attenuation